It is non aljabraic
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

If Tom eats T chocolates, then James eats T-3 and Dave eats T-3+9=T+6.

Together they eat all 45 chocolates: T+T-3+T+6=45.

3T+3=45, T+1=15 (dividing by 3), T=14, Tom eats 14 chocolates.


To solve without algebra: add the 3 chocolates James didn’t eat (compared with Tom) to the total number of chocolates, making 48. Then take away six chocolates (the difference between the 9 Dave ate and the three James didn’t eat) from 48=42. This is now the number of chocolates as if all three ate the same number of chocolates, so we divide 42 by 3=14. So Tom ate 14 chocolates.  



by Top Rated User (717k points)
we need to solve for x, (x being how many tom eats)

Tom eats x pieces of choclate , james eats 3 fewer (x-3) and dave eats 9 more than james (x-3+9)

the equation to solve is x + (x-3) + (x+6) = 45 , 3x = 42 , x= 42/3 = 14

Tom eats 14 pieces

Related questions

Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,493 questions
89,412 answers
8,089 users